In memoriam: the President of the National Academy of Sciences of Ukraine, Director of the E.O. Paton Electric Welding Institute of the National Academy of Sciences of Ukraine Borys Ye Paton (27.11.1918 - 19.08.2020) - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 298